2015
DOI: 10.1093/rheumatology/kev360
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal complications of haematological disease

Abstract: Rheumatological manifestations complicate many benign and malignant blood disorders. Significant advances in haematology, with improved diagnostic techniques and newer musculoskeletal imaging, have occurred in the past two decades. This review focuses on the interrelationship between the major haematological diseases (haemochromatosis, haemophilia, sickle cell disease, thalassaemia, leukaemia, lymphoma, myelodysplastic syndromes, multiple myeloma and cryoglobulinaemia) and rheumatic manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 82 publications
(221 reference statements)
0
9
0
1
Order By: Relevance
“…Hemophilia is an inherited bleeding disorder and has two main types, i.e., hemophilia A that stems from Factor VIII deficiency and hemophilia B that stems from Factor IX deficiency. Many (90%) of the patients with hemophilia develop hemophilic arthropathy before the age of 30 due to recurrent hemarthroses 1485,1486 . Despite the high rate of surgical complications including infection, the number of patients undergoing total joint arthroplasty (TJA) has been rising with increased availability of factor replacement therapy 1481,1487,1488 .…”
Section: Marc Carrier Alex C Spyropoulosmentioning
confidence: 99%
“…Hemophilia is an inherited bleeding disorder and has two main types, i.e., hemophilia A that stems from Factor VIII deficiency and hemophilia B that stems from Factor IX deficiency. Many (90%) of the patients with hemophilia develop hemophilic arthropathy before the age of 30 due to recurrent hemarthroses 1485,1486 . Despite the high rate of surgical complications including infection, the number of patients undergoing total joint arthroplasty (TJA) has been rising with increased availability of factor replacement therapy 1481,1487,1488 .…”
Section: Marc Carrier Alex C Spyropoulosmentioning
confidence: 99%
“…Musculoskeletal presentation has been reported in many malignancies. 9 The most common presentations are myalgia, arthralgia, arthritis, osteolytic bony lesions, and spontaneous fractures. 9 Leukemic arthritis is defined as joint pain and swelling in a diagnosed case of leukemia when other causes of arthritis have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…9 The most common presentations are myalgia, arthralgia, arthritis, osteolytic bony lesions, and spontaneous fractures. 9 Leukemic arthritis is defined as joint pain and swelling in a diagnosed case of leukemia when other causes of arthritis have been excluded. 10 It is reported to occur in around 12 to 65% cases of acute leukemia in children, whereas in adults the reported prevalence is between 4 and 13%.…”
Section: Discussionmentioning
confidence: 99%
“…This study found no statistically significant correlation between the patient's diagnosis and pain, which is consistent with the findings of Gendron et al 20 Bone pain is part of the disease process in almost all multiple myeloma, in some acute leukemia and in other hematological conditions. 24 , 25 We, therefore, aimed to investigate the role of the underlying disease in the pain experience by our participants.…”
Section: Discussionmentioning
confidence: 99%